2020
DOI: 10.1017/s0954579420001443
|View full text |Cite
|
Sign up to set email alerts
|

Addressing educational inequalities and promoting learning through studies of stress physiology in elementary school students

Abstract: To be ready to learn, children need to be focused, engaged, and able to bounce back from setbacks. However, many children come to school with heightened or diminished physiological arousal due to exposure to poverty-related risks. While stress physiology plays a role in explaining how adversity relates to processes that support students’ cognitive development, there is a lack of studies of physiological stress response in educational settings. This review integrates relevant studies and offers future direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 161 publications
(234 reference statements)
1
19
0
Order By: Relevance
“…More in situ work is needed to examine the extent to which our findings are generalizable across different educational settings (Obradović & Armstrong‐Carter, 2020). However, the current findings have real‐life implications for children's developmental trajectories of adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More in situ work is needed to examine the extent to which our findings are generalizable across different educational settings (Obradović & Armstrong‐Carter, 2020). However, the current findings have real‐life implications for children's developmental trajectories of adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the period after critical feedback has ceased may be especially relevant for young students with lower self‐regulatory skills. Educators may consider offering these students support vis‐a‐vis self‐regulation strategies or appraisal strategies in order to minimize potential deleterious effects that prolonged stress arousal can have on health and learning (Obradović & Armstrong‐Carter, 2020). Research in classrooms could clarify whether behavioral self‐regulation and parent‐child co‐regulation explain variability in children's physiological adaptation to receiving critical feedback in real, daily, and educational settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study extends emerging interest in understanding how adolescents' daily prosocial behavior “gets under the skin” (Fuligni & Telzer, 2013), and is linked to the regulation of stress‐physiological systems. Studying stress‐physiology indexed via levels of the hormone cortisol provides unique insight to the ways in which adolescents respond to social experiences that are not readily observable or indicated by self‐report (Obradović & Armstrong‐Carter, 2020), but are meaningfully linked to adolescents' well‐being both concurrently and across the lifespan (Adam et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This effective video tool can be easily employed in home, school, or online settings to introduce children to deep breathing as a self‐regulation technique. We hope this work is just the beginning of a new wave of psychophysiological research that goes beyond understanding how experiences “get under the skin” (Lupien et al., 2001) and has clear, practical implication for supporting child development (Gunnar, 2020; Obradović & Armstrong‐Carter, 2020).…”
Section: Discussionmentioning
confidence: 99%